Budidaya Maggot Sebagai Solusi Pengelolaan dan Pengurangan Sampah Organik di Kota Magelang - Qurotul A’yuni Muawana; Lulu Mirda Fitriani; Hikma May Saroh; Munaa Nur ‘Aziizah (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
The problem of household organic waste remains a major challenge in urban areas, including in the North Rejowinangun Village of Magelang City. High population density and limited land use cause the volume of organic waste to continue to increase and impact the condition of the Final Disposal Site (TPA) which is experiencing overcapacity. This community service activity aims to provide a community-based organic waste management solution through the cultivation of Black Soldier Fly (BSF) maggots as a method of organic waste bioconversion. The implementation method is carried out in a participatory manner through the stages of preparation and problem identification, implementation of activities in the form of education and direct practice of BSF maggot cultivation, as well as monitoring and evaluation. The results of the activity show that BSF maggots are able to decompose household organic waste effectively, as indicated by a reduction in waste volume in a relatively short time and a decrease in potential odor. BSF larvae show stable growth with a high level of waste consumption, especially in media with good humidity and management. In addition to the environmental impact, this activity also increases public knowledge and awareness about the importance of organic waste management and opens up opportunities for the development of maggot cultivation as a productive activity with economic value. Thus, BSF maggot cultivation can be an alternative solution for sustainable organic waste management that is easy to implement in the community.